Analisis Kebutuhan Buku Teks Pendamping Berperspektif Spasial untuk Menstimulus Pemahaman Konsep Spasial - Mubarok, Robby Anzilni; Purwanto, Purwanto; Handoyo, Budi (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2025)
Contextual companion textbooks are needed in geography learning with a spatial perspective as a tool for expressing material so that it can stimulate student’s understanding of spatial concepts. This research aims to analyzed the needs of companion textbooks development reviewed from teachers, students, and curriculum. This type of research is quantitative and descriptive research with questionnaires, interviews, and literature studies as data collection techniques. The research subjects are students in XII grade at SMA Negeri 3 Palembang, SMA Srijaya Negara Palembang, and SMA NU Palembang. The data obtained were analyzed using quantitative descriptive analysis techniques. The results of this study indicate that students have good interest in reading books and good spatial perspective. However, these characteristics are not supported by the main textbooks that have not been compiled with a spatial perspective so that the books have not been able to stimulate student’s understanding of spatial concepts. Based on the needs analysis conducted, it can be concluded that it is necessary to develop companion textbooks with a spatial perspective so that they can stimulate students' understanding of spatial concepts.